Dimensions of Religious Fundamentalism in Theoretical Perspective - Włodarczyk, Rafał (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
The study contains an overview of selected research positions that make up the theory of religious fundamentalism: religious studies researchers, sociologists, political scientists and philosophers, representatives of Western and Polish academic centres. The author sees as assets the differences and divergences between their positions. This gives us a multifold, deepened and advanced understanding of the phenomenon, as well as an insight into which dimensions of this phenomenon is discussed and negotiated in the theory of fundamentalism. Such understanding of fundamentalism can be useful for the pedagogy of religion and general pedagogy, as referred to in the study’s conclusions.
Keywords: religious fundamentalism; ideology; social movements; theory of fundamentalism